PERANAN SEKTOR BASIS TERHADAP PERTUMBUHAN EKONOMI DI KABUPATEN NAGAN RAYA SETELAH TSUNAMI - Yenny Ertika (Universitas Teuku Umar, 2018)
This research aims to determine the role of the base sector in Nagan Raya District after the tsunami. Using Loqation Quetiont (LQ) and Klassen Typology. The purpose of this research is to know the potential sectors and to know the sectors that have comparative and competitive advantages and growth of each sector. This research uses secondary data in the form of data of gross regional domestic product (GRDP) on constant price according to business field. The scope of this research is Nagan Raya District in 2011-2016. Economic growth in Nagan Raya District based on GRDP data has increased every year. The result of the research shows that based on Location Quotient (LQ) analysis of Nagan Raya District sector is agriculture, forestry and fishery sector, mining and quarrying sector. The production of both sectors can not only meet the consumption needs of the relevant areas but also can be exported out of the region. According to Klassen Tipologi analysis, the advanced and growing sectors in Nagan Raya Regency are agriculture, forestry and fishery sector, and construction sector. Keywords: Loqation Quetiont(LQ), Pertumbuhan Ekonomi, Sektor basis, Tipologi Klassen